Creating wealth without labour? Emerging contours of a new techno-economic landscape - Wilfried Lütkenhorst (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
This discussion paper reviews the topical debate around the implications of innovative digital technologies for future patterns of competitiveness, employment, equality, the international division of labour and resource efficiency. It focusses on digital production technologies applied in the manufacturing sector and adopts a global economic perspective in a 10- to 15-year time horizon. The leading research questions are: How is the digital revolution likely to impact the future of industrialisation? How will it affect the relative positions of developed and developing countries in global competition? What are the implications for industrial policy? The paper frames the digitalisation discourse in the context of the changing nature and sequencing of industrialisation (specifically the debate around premature deindustrialisation), its role in latecomer development, and the increasingly complex and blurred intersection between manufacturing and services – the so-called servicification of manufacturing caused by a growing role of embedded and embodied services as well as new service-based business models. In its policy part, the paper contains a detailed case study of the German “Industrie 4.0” strategy and platform. Following a briefer comparative look at similar approaches in selected countries as well as the coordination and harmonisation efforts at the level of the European Union, the paper derives more general conclusions on the role of industrial policy in steering the digital revolution in a socially desirable direction, preventing damaging consequences and promoting its positive impact. Special attention is given to the renewed significance of technology foresight exercises. Finally, the paper provides an outlook on the implications of the digital revolution for the prospects of latecomer industrialisation and the challenges that developing countries in particular are facing.
Keywords: 330; Digitalisierung; Technologie und Innovation